Clinical evaluation of patient with perforation peritonitis and their peritoneal fluid analysis for culture and sensitivity - Srivastava, Rajiv; Singh, Rajeev Kumar (International Surgery Journal, 2018)
Background: Perforation peritonitis is one of the most common emergency that is encountered by surgical unit in emergency department and timely management of it can prevent morbidity and mortality, its important to reach the diagnosis earliest and intervene immediately. we find that understanding the peritoneal fluid obtained on exploratory laparotomy and knowing its culture and sensitivity and treating with appropriate antibiotic has a significant role in better management and early recovery of such patients. Methods: This study comprises of 100 consecutive cases of acute perforation peritonitis on whom exploratory laparotomy was done. In a study period from 1/4/2016 to 13/7/2017 conducted by department of General surgery Government medical college Haldwani-Nanital. Diagnosis was made on basis of clinical and radiological examination. Peritoneal fluid sample was obtained after opening the peritoneum and sent for peritoneal fluid analysis to microbiology department to get culture and sensitivity. Results: Male to female ratio was 3:1 and the most common age group involved was between 20 to 40 years. The most common site of perforation was found to be duodenum amounting to 55% of cases followed by ileal perforation found in 20% cases, gastric perforation was found in 10 % of case. Most common microorganism among Gram negative organism was Klebsella found in 52% cases followed by E. coil in 36% cases, both were found together in 5% cases in rest of the cases proteus and pseudomonas were found. Sensitivity was found to ceftrioxone,ciprofloxacillin and amikacin in more than 87% of gram negative organism while resistance was seen to amplicillin and clotrimoxazole other antibiotics that showed sensitivity to microorganism were Linizoild and minocycline in 76% cases. Around 8% fluid showed presence of methecillin resistant or sensitive Staphylococcus aureus and both were sensitive to linizoilid and minocycline and resistant to penicillin, erythromycin and cephxatin. Conclusions: Peptic ulcer perforation is found to be most common site of perforation where second part of the duodenum supersedes Gastric perforation ratio been 5:1 jointly they are responsible for 65% of perforations. Second most common cause of perforation was due to enteric fever causing ilial perforation which was seen in 20% of the cases. Most common microorganism found is Klebsella and E. coli found in almost 81% of the case and were found to be sensitive to ceftrioxone, amikacin, linizoild and minocycline in almost all the cases.